Asthma and swimming: A meta-analysis - Goodman, M.; Hays, S. (Journal of Asthma, 2008)
In this meta-analysis, studies on swimming and asthma were divided into four groups: Group I compared frequency of asthma among elite swimmers to that of other athletes; Group II examined the association between asthma and swimming during childhood; Group III evaluated effects of swimming programs on asthma severity and pulmonary function; and Group IV compared immediate respiratory effects of swimming to those of other types of exercise. The summary results were expressed as meta-odds ratios (ORs) for binary endpoints such as presence of asthma, and meta-differences for continuous endpoints such as changes in post-exercise pulmonary function tests (PFTs). All summary measures of effect were calculated using random effects models accompanied by a corresponding 95% confidence interval (CI) and a test for heterogeneity. In the analysis comparing frequency of asthma among elite swimmers to that among other athletes (Group I), meta-ORs ranged from 2.3 to 2.6 with all 95% CIs excluding 1.0. The corresponding meta-ORs reflecting the association between asthma and swimming pool use during childhood (Group II) were in the 0.63-0.82 range and were not statistically significant. In comparison to swimming, running and/or cycling was associated with a statistically significant four-to six-fold increase in exercise induced bronchospasm. Although asthma is more commonly found among elite swimmers than among other high-level athletes, it is premature to draw conclusions about the causal link between swimming and asthma because most studies available to date used cross-sectional design, because the association is not confirmed among non-competitive swimmers, and because asthmatics may be more likely to select swimming as the activity of choice because of their condition.